2014
DOI: 10.1108/jbs-10-2013-0096
|View full text |Cite
|
Sign up to set email alerts
|

Messing with corporate heads? Psychological contracts and leadership integrity

Abstract: Purpose – The purpose of the paper is to present a model of leadership fulfiling the need of our times: The leadership psychological contract (LPC). In the current socio-economic environment of uncertainty and unprecedented change, both business environments and the community at large are marked by leadership crises. This instability makes an understanding of the relational aspects impacting the relationship between leaders and their constituencies both important and urgent. Now, more than ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In addition, we found that leader credibility surfaced in peer-reviewed journals representing a wide range of disciplines: public administration (Grasse et al 2014 ; Gabris et al 2001 ), business strategy (Salicru and Chelliah 2014 ), economics (Komai and Stegeman 2010 ), business management (Chun et al 2014 ; Kouzes and Posner 2005 ), sports management (Swanson and Kent 2014 ), political science (Myerson 2008 ; Van Zuydam and Hendriks 2018 ), medical and health services (Davidhizar 2007 ; Loh et al 2016 ), education (Bolkan and Goodboy 2009 ; Holland 1997 ), and psychology (Sweeney et al 2009 ). Empirical research has explored relationships between leader credibility and various outcomes, such as leader self-awareness (Grasse et al 2014 ), subordinate burnout (Gabris and Ihrke 1996 ), managerial innovation (Gabris et al 1999 ), motivating language (Holmes and Parker 2017 ), subordinates’ perceived cost of seeking feedback (Chun et al 2014 ), and affective well-being at work (Rego and Pina e Cunha 2012 ).…”
Section: Introductionmentioning
confidence: 90%
“…In addition, we found that leader credibility surfaced in peer-reviewed journals representing a wide range of disciplines: public administration (Grasse et al 2014 ; Gabris et al 2001 ), business strategy (Salicru and Chelliah 2014 ), economics (Komai and Stegeman 2010 ), business management (Chun et al 2014 ; Kouzes and Posner 2005 ), sports management (Swanson and Kent 2014 ), political science (Myerson 2008 ; Van Zuydam and Hendriks 2018 ), medical and health services (Davidhizar 2007 ; Loh et al 2016 ), education (Bolkan and Goodboy 2009 ; Holland 1997 ), and psychology (Sweeney et al 2009 ). Empirical research has explored relationships between leader credibility and various outcomes, such as leader self-awareness (Grasse et al 2014 ), subordinate burnout (Gabris and Ihrke 1996 ), managerial innovation (Gabris et al 1999 ), motivating language (Holmes and Parker 2017 ), subordinates’ perceived cost of seeking feedback (Chun et al 2014 ), and affective well-being at work (Rego and Pina e Cunha 2012 ).…”
Section: Introductionmentioning
confidence: 90%
“…Leaders contribute to the psychological conditions experienced by employees in the workplace. Salicru and Chelliah (2014) stated that transformational leadership applies a relational contract, whereas transactional leadership focuses on the monetary features of the relationship. A transformational leadership style is focused on the needs of others rather than self-interest, expectations are clearer and the vision is understood (Lee Whittington & Galpin, 2010).…”
Section: Leadership Stylementioning
confidence: 99%
“…Leaders can play a significant role in the psychological conditions that influence employee attitudes and performance (Erkutlu & Chafra, 2013; Philipp & Lopez, 2013). Whilst the relationship is important, “no contemporary approach to leadership has explicitly considered using the psychological contract as a framework to fully understand this leader-follower relationship” (Salicru & Chelliah, 2014, p. 39). Leaders can develop a diverse range of relationships with differing degrees of support and perceived trust.…”
Section: Psychological Contractsmentioning
confidence: 99%
“…Psychological contracts are beliefs or perceptions that are ongoing, dynamic and implicit in human nature, based on the principle of reciprocity and exchange. Psychological contracts that are primarily driven by the economic exchange are transactional in nature, whereas those driven by socio-emotional aspects are relational in nature and the exchanges that are driven by principle or cause, not limited to self-interest, are ideological in nature (Salicru and Chelliah, 2014;Thompson and Bunderson, 2003). It is therefore a useful guide for contractarian ethics (Donaldson and Dunfee, 1994) which is also central to the literature of grassroots communities being exploited under the neoclassical and utilitarian approach.…”
Section: Pctmentioning
confidence: 99%